Effect of Mercerisation Soaking Time and Concentration on Tensile Properties of Pentaclethra macrophylla Fibre Reinforced Composite for Automotive Application - Okechukwu, Chikelu Peter; Ekene, Ilechukwu Anthonia; Chimezie, Anyaora Sunday; Amaechi, Okafor Anthony; Ndubuisi, Okoye Chibuzor (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
Lately, there has been a growing global awareness about the negative impact of synthetic fibres and the need for replacement with eco-friendly, plant-based natural fibres. However, the hydrophilic nature of these natural fibres can create compatibility issues with various matrices, which limits their use. This has sparked an increased research interest in finding an effective mercerization process to modify the surface of these plant-based fibres, ultimately enhancing their mechanical properties. In this study, fruit fibres from the Pentaclethra macrophylla plant was processed, experimented with NaOH soaking times of 1 hour, 3 hours, and 5 hours, along with treatment concentrations of 2%, 5%, and 8% by weight. The tensile properties of the composite made from these processed fibres were examined, and statistical analysis using one-way analysis of variance (ANOVA) and regression in Minitab software was conducted. The results showed a 21% decrease in tensile strength and a 32% increase in elastic modulus as the soaking time increased from 1 hour to 5 hours. Additionally, increasing the NaOH treatment concentration from 2% to 8% led to enhancements in both tensile strength and elastic modulus. This study shows that the tensile properties of the fiber composite are greatly impacted by both the soaking time and NaOH concentration. Therefore, optimising the parameters of the mercerisation process can enhance these properties, making the Pentaclethra M. fibre-reinforced composite a viable option for automotive applications.